Occupational injury among migrant workers in China: a systematic review. Issue 5 (24th May 2013) - Fitzgerald, Simon; Chen, Xin; Qu, Hui; Sheff, Mira Grice
Abstract : Objectives: This review considers the state of occupational injury surveillance and prevention among migrant workers in China and suggests areas of focus for future research on the topic. Methods: Bibliographic databases were searched for qualitative and quantitative studies on surveillance of and interventions to prevent occupational injury among migrant workers in mainland China. Additional abstracts were identified from the citations of relevant articles from the database search. Studies fitting the inclusion criteria were evaluated, and findings were extracted and summarised. Results: The search uncovered 726 studies in the English-language databases searched, and 3109 in the Chinese database. This article analyses a total of 19 research articles that fit the inclusion criteria with qualitative or quantitative data on occupational injury surveillance and prevention of migrant workers in China. Despite evidence of the vulnerability of migrant workers in the workplace, there is little systematic surveillance of occupational injury and few evaluated interventions. Conclusions: Migrant workers account for a disproportionate burden of occupational injury morbidity and mortality in China. However, data are inconsistent and inadequate to detail injury incidence or to evaluate interventions. The following are suggestions to decrease injury incidence among migrants: strengthen the national system of occupational injury surveillance; focus surveillance and interventions on high-risk occupations employing migrants such as construction, manufacturing and small mining operations; improve occupational safety training and access to appropriate safety equipment; evaluate recent changes in occupational health and safety and evaluate outcome of multi-party interventions to reduce occupational injury among migrant workers.